Leakage current reduction in CMOS VLSI circuits by input vector control. - Abdollahi, A. (IEEE Transactions on VLSI systems)
The first part of this paper describes two runtime mechanisms for reducing the leakage current of a CMOS circuit. In both cases, it is assumed that the system or environment produces a "sleep" signal that can be used to indicate that the circuit is in a standby mode. In the first method, the "sleep" signal is used to shift in a new set of external inputs and pre-selected internal signals into the circuit with the goal of setting the logic values of all of the internal signals so as to minimize the total leakage current in the circuit. This minimization is possible because the leakage current of a CMOS gate is strongly dependent on the input combination applied to its inputs. In the second method, nMOS and pMOS transistors are added to some of the gates in the circuit to increase the controllability of the internal signals of the circuit and decrease the leakage current of the gates using the "stack effect". This is, however, done carefully so that the minimum leakage is achieved subject to a delay constraint for all input-output paths in the circuit. In both cases, Boolean satisfiability is used to formulate the problems, which are subsequently solved by employing a highly efficient SAT solver. Experimental results on the combinational circuits in the MCNC91 benchmark suite demonstrate that it is possible to reduce the leakage current in combinational circuits by an average of 25% with only a 5% delay penalty. The second part of this paper presents a design technique for applying the minimum leakage input to a sequential circuit. The proposed method uses the built-in scan-chains in a VLSI circuit to drive it with the minimum leakage vector when it enters the sleep mode. The use of these scan registers eliminates the area and delay overhead of the additional circuitry that would otherwise be needed to apply the minimum leakage vector to the circuit. Experimental results on the sequential circuits in the MCNC91 benchmark suit show that, by using the proposed method, it is possible to reduce the leakage by an average of 25% with practically no delay penalty.